Self-control and stress-coping strategies in sports - Belozerova, L. A.; Bragina, E. A.; Semenova, I.A.; Semikasheva, I. A. (Theory and Practice of Physical Culture, 2018)
In modern sport science a high priority is being given to the studies of self-control skills viewed as the individual ability to control own emotional, physical and internal responses. It should be noted that many issues of the sport stress control and coping strategies are still virtually unexplored. The study was designed to test the assumption that the systemic sporting practices help develop self-control skills and constructive stress-coping strategies viewed among the best personality qualities for the sport careers. The study data were used for a comparative analysis of the self-control skills and stress-coping strategies in sporting students (qualified Candidate Masters of Sports and high-class athletes) versus their non-sporting peers aged 19 years on average. The study data and analysis showed the sporting students making high progress in the self-control and stress-coping strategies development aspects.